Indicators of sustainable development on the local and regional level: Experiences and requirements for further development: Results of a national survey - Gehrlein, Ulrich (Raumforschung und Raumordnung | Spatial Research and Planning, 2002)
The article presents results obtained in the frame of a survey realised on local (cities and municipalities) and regional level (counties) in Germany to analyse the status quo and experiences made on the development and application of “sustainability indicators”. The research focuses on the conceptual orientation, implementation and application of the indicator systems in current communal activities. Based on this analysis the appropriateness of the indicator system, its critical features and success factors, evaluated from the interviewees’ point of view, are discussed. Finally design criteria for the development and the application of the indicator systems are deducted.
Keywords: Article